2020
DOI: 10.14689/ejer.2020.89.9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Working in Public or Private Schools on Job Satisfaction of Teachers in Turkey: A Meta-Analysis Study

Abstract: The main problem of this study is to investigate whether the school type (private/public) has any effects on job satisfaction of teachers or not to reveal the effects of the school type (private/public) on job satisfaction of teachers in Turkey.Research Methods: In this study, as one of the research synthesis methods, the meta-analysis method was used. In the analysis of the data, one of the group comparison meta-analysis methods, the Group Difference Method was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The results of the research regarding the differences in satisfaction levels between public and private school teachers are consistent with other studies on job satisfaction and leadership styles in public and private institutions, where it was concluded, through statistical tests, no parametric (Mann-Whitney U), significant differences noticed between the job satisfaction levels between teachers from private schools with state contribution and public schools, observing a higher satisfaction in the sample of teachers from private schools (Chiang et al, 2014). Likewise, a meta-analysis carried out in Turkey on the effects on public or private schools teachers regarding teachers' job satisfaction, in which, after analyzing 43 studies, it was determined that teachers from private institutions had job satisfaction at increased levels compared to the teachers, who worked in public institutions (Aytac, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the research regarding the differences in satisfaction levels between public and private school teachers are consistent with other studies on job satisfaction and leadership styles in public and private institutions, where it was concluded, through statistical tests, no parametric (Mann-Whitney U), significant differences noticed between the job satisfaction levels between teachers from private schools with state contribution and public schools, observing a higher satisfaction in the sample of teachers from private schools (Chiang et al, 2014). Likewise, a meta-analysis carried out in Turkey on the effects on public or private schools teachers regarding teachers' job satisfaction, in which, after analyzing 43 studies, it was determined that teachers from private institutions had job satisfaction at increased levels compared to the teachers, who worked in public institutions (Aytac, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Tolliver’s (2018) study reported that job title helps to increase primary school teachers’ job satisfaction. Aytac’s (2020) study identified that job title significantly affects job satisfaction of teachers in both public and public schools. Some previous studies have found that there may also be gender differences in teachers’ job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, it was emphasized that there is a positive relationship between teacher autonomy and the cooperative management style of school administrators; thus, it is probable that teacher autonomy is a significant predictor of professionalism (Akçay & Sevinç, 2021;Karatay, Günbey & Taş, 2020). Furthermore, in a recent meta-analysis study by Aytaç (2020) in which 43 studies have been examined, it has been highlighted that supporting teacher autonomy can have positive effects on job satisfaction. A study in a similar vein, Şentürken & Oğuz (2020) pointed out that teachers' job satisfaction and autonomy are correlated in the sub-dimensions of autonomy although the levels of them differ.…”
Section: Koçakmentioning
confidence: 99%